Development Modes of Typical Urban Rail Transit Interconnection in Foreign Cities and Implications - HOUATI·Yeerjiang; YE Xiafei; WANG Zhenbo; CHENG Yan (Chengshi guidao jiaotong yanjiu)
［Objective］ Despite the current established rail transit networking operation in cities like Beijing, Shanghai and Guangzhou, usually the independent operation of each line leads to high pressure and uneven distribution of resources at transfer stations, it is necessary to draw on the experience of foreign cities in typical rail transit interconnection to provide references for the development mode of urban rail transit interconnection in Chinese cities. ［Method］ With the urban rail transit lines in cities like Tokyo, Paris and Karlsruhe as the research objects, the background and development modes of their interconnection are investigated and analyzed, the basic characteristics are summarized. ［Result & Conclusion］ As the typical urban rail transit interconnection modes in the above-mentioned cities emerge in different contexts, whether to adopt these modes or not should be decided based on the actual situation in China. The typical interconnection in foreign cities mainly exists among lines on the same passenger flow corridor, and basically not at the level of urban rail transit network. Therefore, in the implementation of interconnection, renovation of the existing operating lines should not be considered unless the renovation cost is low and the impact is small. The newly-built lines should use the technical standards that are consistent with those of the existing lines. In the interconnection of urban rail transit, dual-system trains are only suitable among existing rail transit lines with different systems in order to save costs.